Perspectives of colombian patients with psoriasis on access to treatment and its repercussion on the social environment. An experience of Fundapso (2019)
ABSTRACT: Background: Psoriasis affects 2% of the Colombian population (1); in addition to skin lesions, the quality of life in these patients is too affected (2), there is a greater burden of disease associated with the costs of treatment and medical care, in addition, comorbidities are associated with low self-esteem, social stigma and obstacles in obtaining employment (3). Objectives: To describe the perspectives on access to treatment and the impact on different settings of Colombian patients with psoriasis through an online survey. Methods: An online survey was conducted in collaboration with the Latin American Psoriasis Alliance (ALAPSO) between September 2014 and March 2015. The sample corresponded to 312 people diagnosed with psoriasis in Colombia and affiliated to the Foundation for the Support of Patients with Psoriasis (FUNDAPSO). It was investigated for demographic characteristics, perception of treatment and access to it, as well as its impact on work, social, family and personal. Results: 55% of those surveyed were men, aged between0- > 61 years. The most frequent type of psoriasis was of the vulgar type 68%; 30% was formulated with biological therapy, but does not have access to it. The 23% of the patients described not being guided by the doctor to treat the disease; the 20% perceived some type of discrimination in the field of study or work, the 24% describe that the psoriasis affected the development of social and recreational activities, the 33% indicated that the disease has affected it in a negative way, and the 23% have felt affected in the development of their sexual life. In mental health, 68% have felt depressed and 55% expressed sadness, but only 28% have received psychological attention. When they have psoriasis under control 28.8% feel calm and 12% feel happy. Low levels of care and access to adequate treatment are evident from the patient’s perspective. According to the patient’s perception, psoriasis generates a negative impact at the psychosocial level. It is important that the health system considers not only the biological component affected by the disease, but also the high psychosocial burden.